2015
DOI: 10.1016/j.soildyn.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of motorway bridges accounting for key structural components and nonlinear soil–structure interaction

Abstract: Seismic analysis of motorway bridges accounting for key structural components and nonlinear soil-structure interaction Anastasopoulos, Ioannis; Sakellariadis, L.; Agalianos, A. Sakellariadis, L., & Agalianos, A. (2015). Seismic analysis of motorway bridges accounting for key structural components and nonlinear soil-structure interaction. Soil Dynamics and Earthquake Engineering, 78, 127-141. DOI: 10.1016/j.soildyn.2015 General rights Copyright and moral rights for the publications made accessible in Discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Soil-structure interaction (SSI) may have a significant effect on the seismic damage of a bridge, and should be taken into account. Such a simplified method accounting for SSI is presented in Anastasopoulos et al [2015].…”
Section: Overview Of the Rare Systemmentioning
confidence: 99%
“…Soil-structure interaction (SSI) may have a significant effect on the seismic damage of a bridge, and should be taken into account. Such a simplified method accounting for SSI is presented in Anastasopoulos et al [2015].…”
Section: Overview Of the Rare Systemmentioning
confidence: 99%
“…In Anastasopoulos et al, 7 the validity of the simplified model was confirmed using 30 real records as seismic excitation, covering a wide range of intensities and kinematic characteristics. The efficiency of the simplified modelling technique was shown to be insensitive to record selection.…”
Section: Outline and Key Assumptionsmentioning
confidence: 85%
“…For the interfaces between the retaining wall and the embankment, a maximum shear capacity of 0.5S u is considered in the case of a cohesive embankment Powrie. 7,18 Initially, the effect of abutment stoppers of negligible clearance is examined. A reinforced-earth embankment is considered, as it is quite common for such motorway bridges; it is modelled in a simple manner, applying kinematic constraints in the transverse direction.…”
Section: Effect Of Abutment Stoppersmentioning
confidence: 99%
See 1 more Smart Citation
“…The seismic excitation is applied at the base of the model. More details on the development of the rigorous model can be found in the study by Anastasopoulos et al (2011Anastasopoulos et al ( , 2015.…”
Section: Conventional Systemmentioning
confidence: 99%